Experimental Assessment of the Out-of-Plane Performance of Masonry Buildings Through Shaking Table Tests - Candeias, P. X. (2016)
This article presents the results of the LNEC-3D shaking table tests on two mock-ups, Brick House and Stone House, carried out in the scope of the workshop “Methods and challenges on the out-of-plane assessment of existing masonry buildings.” The mock-ups have a U shape with one facade wall and two orthogonal sidewalls. The facade has a central opening and a gable on top, whereas the two sidewalls, acting as abutments, are either blind or have a window. A unidirectional seismic action, in the perpendicular direction to main wall, was applied. Out-of-plane behavior of the facade was found, even if the response was clearly influenced by the presence of the window in one of the sidewalls, which led to significant torsion of the structure. The detailed description of the two tests and the conclusions are presented. The response of the mock-ups was evaluated based on the displacements, damage, and collapse mechanisms developed as function of an increasing intensity earthquake testing protocol, in which a pre-processed strong ground motion component of the Christchurch (New Zealand) earthquake (February 21, 2011) was used.